Applications of Lysozyme, an Innate Immune Defense Factor, as an Alternative Antibiotic - Patrizia Ferraboschi; Samuele Ciceri; Paride Grisenti (MDPI AG, 2021)
Lysozyme is a ~14 kDa protein present in many mucosal secretions (tears, saliva, and mucus) and tissues of animals and plants, and plays an important role in the innate immunity, providing protection against bacteria, viruses, and fungi. Three main different types of lysozymes are known: the c-type (chicken or conventional type), the g-type (goose type), and the i-type (invertebrate type). It has long been the subject of several applications due to its antimicrobial properties. The problem of antibiotic resistance has stimulated the search for new molecules or new applications of known compounds. The use of lysozyme as an alternative antibiotic is the subject of this review, which covers the results published over the past two decades. This review is focused on the applications of lysozyme in medicine, (the treatment of infectious diseases, wound healing, and anti-biofilm), veterinary, feed, food preservation, and crop protection. It is available from a wide range of sources, in addition to the well-known chicken egg white, and its synergism with other compounds, endowed with antimicrobial activity, are also summarized. An overview of the modified lysozyme applications is provided in the form of tables.